Pemekaran Daerah Luwu Raya Sebagai Isu Kampanye Pemilihan Gubernur Sulawesi Selatan - Suhardiman Syamsu; Reksa Burhan; Ade Irma Surani Haliq (Sospol : Jurnal Sosial Politik, 2020)
Regional expansion is argued to improve people's welfare, the quality of public services, create good and efficient local government, and build substantive democracy at the local level. Regional expansion must consider aspects of urgency and capacity. The policy process for regional expansion in Indonesia is bottom-up and is dominated by a political process rather than an administrative process. This issue raised in the momentum of the Pilkada, but until the 2018 period it had not yet been realized. This study aims to explain the issue of regional expansion of Luwu Raya during the regional elections for Governor and the Vice Governor of South Sulawesi in 2009, 2013 and 2018 and the obstacles. Data obtained from official government documents and reports. The data presented is the result of the clustering process, descriptive analysis of interview transcripts and processed as research results. The relationship between the elite is the focus of the analysis in this study. Researchers further explore the political dynamics of local elites in the discourse of regional expansion. It examines the issue of regional expansion becomes a political campaign maneuver aims to collect electoral votes. The concept of decentralization does not made the political process of regional expansion easily to realize. The practice of decentralization governance not only changing the implementation of governance in the regional administrative but also the implementation of politics at the local level. Political elites compete for electoral barns as a manifestation of local political practices that coincide with the issue of regional expansion.